The new accountability : environmental responsibility across borders - Mason, Michael, 1966- (EARTHSCAN, 2005)
"Drawing on case studies, this book provides a fresh understanding of democratic accountability for transboundary and global harm and argues that environmental responsibility should be established in open public discussions about harm and risk"--Provided by publisher.